Analysis of Interconversion between Atropisomers of Chiral Substituted 9, 9'‐Bicarbazole. Issue 3 (9th December 2020) - Kobayashi, Toshifumi; Ishiwari, Fumitaka; Fukushima, Takanori; Hanaya, Kengo; Sugai, Takeshi; Higashibayashi, Shuhei
Abstract: Interconversion of atropisomers of chiral 3, 3'‐di‐ tert ‐butyl‐9, 9'‐bicarbazole linked by a single N−N bond was analyzed by DFT calculations and experiments. The calculations revealed that the trans transition state has a lower energy for the interconversion than the cis transition state. The lowest transition state of interconversion between natural dixiamycins A and B containing a 9, 9'‐bicarbazole structure was found to be the trans transition state. The calculations also indicated that degradation through N−N bond cleavage was faster than racemization. Atropisomeric enantiomers of 3, 3'‐di‐ tert ‐butyl‐9, 9'‐bicarbazole were resolved by chiral HPLC for the first time, and then racemization and N−N bond cleavage were investigated by heating experiments, showing that racemization did not take place below the degradation temperature. Abstract : The atropisomeric enantiomers of chiral substituted 9, 9'‐bicarbazole linked by a N−N bond were resolved by chiral HPLC for the first time. DFT calculations and heating experiments clarified that racemization did not take place below the temperature for N−N bond cleavage.